Risk Premia and the Dynamic Covariance between Stock and Bond Returns - Scruggs, John T.; Glabadanidis, Paskalis (Journal of Financial and Quantitative Analysis, 2003)
John T. Scruggs, Paskalis Glabadanidis, Risk Premia and the Dynamic Covariance between Stock and Bond Returns, The Journal of Financial and Quantitative Analysis, Vol. 38, No. 2 (Jun., 2003), pp. 295-316